AB0631 Prevalence, Severity and Clinical Significance of Pain in Patients with Systemic Sclerosis. (15th July 2016) - Ostojic, P.; Jankovic, K.; Djurovic, N.; Stojic, B.; Knezevic-Apostolski, S.; Bartolovic, D.
Abstract : Objectives: To assess prevalence, severity and type of pain in patients with systemic sclerosis (SSc), and relationship with disease status, depression and quality of life. Methods: 42 consecutive patients with SSc (38 women and 4 men), mean age 56.5 years, mean disease duration 9.5 years, were included in this study. 31 (73.8%) of patients had limited SSc (lSSc) and 11 (26.2%) diffuse form of disease (dSSc). ACA were positive in 15 (35.7%) and ATA in 17 (40.5%) patients. We assessed prevalence and severity of different types of pain (during attacks of Raynaud's phenomenon, pain caused by ischemic ulcers, odynophagia, arthralgia, headache, back pain and chest pain) in our patients. Presence of manifestations of neuropathic pain was assessed using the PainDetect questionnaire. Relationship among different types of pain with disease status, symptoms of depression and quality of life was estimated. Disease status was assessed using the Scleroderma Assessment Questionnaire (SAQ), occurrence of depressive symptoms by the Beck's Depression Inventory (BDI), whilst quality of life was evaluated using the EQ-5D index. Results: Thirty nine patients (92.9%) reported different types of pain. 19 (45.2%) patients experience some form of pain every day. Arthralgia is the most common type of pain, present in 78.6% of patients, followed by pain during attacks of Raynaud's phenomenon (69%), back pain (47.6%), headache (31%), chest pain (23.8%), odynophagia (21.4%) and painful ischemic ulcers (19%). Pain caused by ischemic ulcers was reported as most severe (median 8.5 on a 0–10 scale). All types of pain were equally frequent in patients with lSSc and dSSc. However, joint pain was more intense (p=0.02) in patients with dSSc (7.6 vs. 5.5). The Index of Disease Statuts (IDS) positively correlated with severity of joint pain (ρ=0.66, p<0.001), but not with severity of other types of pain. Moreover, a significant correlation was noticed only between joint pain and the EQ-5D index (ρ=-0.52, p=0.009). On the other hand, a significant correlation between BDI index and intensity of pain during attacks of Raynaud phenomenon (ρ=0.49, p=0.007), pain caused by ischemic ulcers (ρ=0.81, p=0.016), odynophagia (ρ=0.73, p=0.026) and arthralgia (ρ=0.59, p<0.001) was observed. Compared to patients with intermittent pain, patients suffering from chronic pain have a significantly lower mean value of EQ-PD index (0.52 vs 0.79, z=-4.12, p<0, 001) and a higer mean value of IDS (1.21 vs. 0.53, z=-3.32, p=0.001). Patient with manifestations of neurpathic pain have significantly higher mean values of IDS, BDI an EQ-5D index, than patients without neuropathic pain. Conclusions: Pain is present in 92.9% of patients with SSc. Arthralgia is the most common type of pain. Although less frequent, pain caused by ischemic ulcers was reported as most severe. Intense joint pain, chronic pain and neuopathic pain are associated with more severe form of the disease and poorer quality of life. All types of pain have impact on development of depressive symtoms in patients with SSc. Disclosure of Interest: None declared